Berberine: A Promising Treatment for Neurodegenerative Diseases - Cheng, Ziqian; Kang, Chenglan; Che, Songtian; Su, Jingyun; Sun, Qihan; Ge, Tongtong; Guo, Yi; Lv, Jiayin; Sun, Zhihui; Yang, Wei; Li, Bingjin; Li, Xin; et al. (Frontiers in Pharmacology, 2022)
Berberine, as a natural alkaloid compound, is characterized by a diversity of pharmacological effects. In recent years, many researches focused on the role of berberine in central nervous system diseases. Among them, the effect of berberine on neurodegenerative diseases has received widespread attention, for example Alzheimer's disease, Parkinson's disease, Huntington's disease and so on. Recent evidence suggests that berberine inhibits the production of neuroinflammation, oxidative and endoplasmic reticulum stress. These effects can further reduce neuron damage and apoptosis. Although the current research has made some progress, its specific mechanism still needs to be further explored. This review provides an overview of berberine in neurodegenerative diseases and its related mechanisms, and also provides new ideas for future research on berberine.